A Composite Risk Indicator for Business Sectors Involving Excisable Goods: A Romanian Case Study - Cristina TIMOFTE (COCA); Nicoleta-Iulia POPESCU (BODEA); Veronica GROSU; Dan-Andrei COCA; Simona-Maria TANASA (BRINZARU) (Communications of International Proceedings, 2023)
The main purpose of this article is to conduct a scientific statistical research on accounting, financial and tax risk assessment for economic activities involving excisable products by developing a composite risk indicator. The necessity of such an instrument resides in the void in the literature for this particular business sectors in what concerns the accounting, financial and tax risk mapping. As a research methodology, a cross-sectional analysis was performed for the time period 2017 - 2021 of variables consisting of financial ratios calculated on the basis of data and information from the annual financial statements submitted by a number of 309 economic operators operating in five economic business sectors, involving excisable products: alcoholic beverages, wine from grapes, beer and, petroleum products. The research’s results revealed that the areas of critical vulnerability in terms of general accounting, financial and tax risk are in the business sector: Manufacture of products from petroleum processing, followed by Distilling, refining and blending of alcoholic beverages. The composite risk indicator was used in order to elaborate a temporal profile for each analyzed business sector. These profiles showed that the highest risk levels were recorded in 2017 – 2018, years when individual consumption increased and the lowest levels in 2020, year characterized by the COVID pandemic, when a significant decrease in all economic activities at national level were recorded. Other findings were that the most significant and useful financial ratios for risk mapping for the analyzed business sectors are: Inventories in Turnover and Net Profit in Equity
Keywords: Accounting risk; composite risk indicator; excisable goods; financial and tax risk